Cochlear Sox2+ Glial Cells Are Potent Progenitors for Spiral Ganglion Neuron Reprogramming Induced by Small Molecules - Chen, Zhen; Huang, Yuhang; Yu, Chaorong; Liu, Qing; Qiu, Cui; Wan, Guoqiang (Frontiers in Cell and Developmental Biology, 2021)
In the mammalian cochlea, spiral ganglion neurons (SGNs) relay the acoustic information to the central auditory circuits. Degeneration of SGNs is a major cause of sensorineural hearing loss and severely affects the effectiveness of cochlear implant therapy. Cochlear glial cells are able to form spheres and differentiate into neurons in vitro. However, the identity of these progenitor cells is elusive, and it is unclear how to differentiate these cells towards functional SGNs. In this study, we found that Sox2+ subpopulation of cochlear glial cells preserves high potency of neuronal differentiation. Interestingly, Sox2 expression was downregulated during neuronal differentiation and Sox2 overexpression paradoxically inhibited neuronal differentiation. Our data suggest that Sox2+ glial cells are potent SGN progenitor cells, a phenotype independent of Sox2 expression. Furthermore, we identified a combination of small molecules that not only promoted neuronal differentiation of Sox2- glial cells, but also removed glial cell identity and promoted the maturation of the induced neurons (iNs) towards SGN fate. In summary, we identified Sox2+ glial subpopulation with high neuronal potency and small molecules inducing neuronal differentiation towards SGNs.